(untitled) (Research, Society and Development, 2021)
Herpes zoster is a viral infection caused by the reactivation of the varicella-zoster virus, which generally affects the elderly population. The varicella virus, when in a dormant state, is located in the trigeminal ganglia and when reactivated can cause lesions on the face and intraoral vesicles. This disease can affect immunosuppressed patients with greater prevalence and is characterized by maculopapular eruptions distributed in the region of the affected nerve, causing severe pain, tremors and even paresthesia. The diagnosis of herpes zoster is usually established through the clinical picture presented by the patient and the treatment is focused on the symptoms and the cause, opting for the use of systemic and topical antiviral medications. This article reports the case of a female patient, caucasian, without health problems and previous immunosuppressive treatments, 56 years old, who came to the emergency room, with the main complaint of extra oral pain in the right hemiface, with rapid evolution of three days after extraction.